Investigation of the visual components of Xwarrah in the Elymais reliefs of Tang-e Sarvak - Raiygani, Ebrahim; Basafa, Hasan; Veisi, Mahsa; Kheradmand Nik, Marziyeh (Вестник Томского государственного университета. Культурология и искусствоведение)
Xwarrah was one of the essential components of the legitimate government in an-cient Iran. Tang-e Sarvak's Elymais reliefs have been one of the places to show the political and religious legitimacy of the local Elymais dynasty. The present study aims to explain the various instances of Xwarrah in Tang-e Sarvak. The necessity of conducting this research is to identify the missing link of Xwarrah's political and religious components. This article has tried to answer the following questions: what are the most important visual components used to portray the Xwarrah in the reliefs of Tang-e Sarvak? what was the purpose of creating such features by the Elymais? As a result, the collection of Tang-e-Sarvak reliefs displayed the political and religious concepts of Xwarrah in the form of some symbols. The present study's data results from authors' survey studies and citation studies, and we have examined them through historical, descriptive analysis.